Within-country heterogeneity in patterns of social contact relevant for tuberculosis infection transmission, prevention, and care. - Kate E LeGrand; Anita Edwards; Mbali Mohlamonyane; Njabulo Dayi; Stephen Olivier; Dickman Gareta; Robin Wood; Alison D Grant; Richard G White; Keren Middelkoop; Palwasha Khan; Nicky McCreesh (PLOS Global Public Health, 2025)
Mycobacterium tuberculosis (Mtb) transmission is driven by variable social, environmental, and biological factors, including the number and duration of indoor contacts. Social contact data can provide information on potential transmission patterns, but is underutilised outside the field of mathematical modelling. We explore three contexts where contact data can provide valuable insights: 1) household contact tracing; 2) infection prevention and control measures (IPC); and 3) contamination in cluster randomised trials (CRTs). A social contact survey was conducted in adults aged 18 and older from three communities with comparable population sizes in South Africa: an urban township and peri-urban and rural clinic catchment areas. Participants reported congregate settings visited over 24-hours, visit durations, and estimated number of people present. To correspond with the three contexts, we estimated the proportion of contact hours occurring 1) within the home; 2) in congregate settings outside the home; and 3) outside the participants' communities. Participants reported a mean of 27.0 (rural), 55.2 (peri-urban), and 73.0 (urban) contact hours. The proportions of household contact were similar among rural and peri-urban participants (76.8% and 71.7%), compared to urban (48.6%). Congregate settings visited varied; urban participants spent the most contact hours in retail/office settings (19.9%), peri-urban participants in community-service buildings (20.4%), and rural participants in other peoples' homes (25.5%). Urban participants reported the highest proportion of contact outside the community (67.0%) compared to rural (38.8%) and peri-urban (21.5%) participants. The observed heterogeneity in contact patterns has implications for TB interventions. Household contact tracing may be most effective in the rural community where household contact was highest. The diverse range of congregate settings visited suggests that prioritising IPC measures in these locations may enhance their overall efficacy. Considering contact patterns when designing clusters may reduce contamination in CRTs. Tailored interventions, informed by local contexts, are essential to reduce TB burden.